Usability, Accessibility and User Experience Evaluation of ADA Blocks by HCI Experts - Perin, Ana Paula Juliana; Eive dos S. Silva, Deivid; M. C. Valentim, Natasha (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2025: Anais do XXIV Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2025)
Introduction: Educational technologies have been important in supporting the teaching and learning process. Objective: In this context, this paper presents a study evaluating the usability, accessibility, and user experience of the ADA Blocks virtual assistent that was designed to recommend block programming tools for teachers. Methodology or Steps: Ten HCI experts participated in this study, seeking to identify improvements and promote more effcient and satisfactory interactions for this assistant. Results: Problems such as design inconsistencies, lack of responsiveness on mobile devices, navigation diffculties, and accessibility barriers, among others, were identified. These findings enable improvements to ensure that ADA Blocks can be effective, inclusive, and generate a good experience for its users.